Photodynamic Therapy From Theory to Application - Abdel-Kader, Mahmoud H.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Photodynamic Therapy: From Theory to Application brings attention to an exceptional treatment strategy, which until now has not achieved the recognition and breadth of applications it deserves. The authors, all experts and pioneers in their field, discuss the history and basic principles of PDT, as well as the fundamentals of the theory, methods, and instrumentation of clinical diagnosis and treatment of cancer. Non-oncological applications such as the use of PDT in control of parasites and noxious insects are also discussed. This book serves as a standard reference for researchers and students at all levels, clinical specialists interested in the topic and those in industry exploring new areas for development. A comprehensive exposition of both the theory and application of PDT, this book fills the gaps in the current literature by bringing together both basic understanding of the process of PDT and an expanded vision of its applications.
Part I History -- History of Photodynamic Therapy -- Part II Theory and Mechanism -- Fundamentals of Photophysics, Photochemistry and Photobiology -- Molecular Biological Mechanisms in Photodynamic Therapy -- Part III Methods and Instrumentation -- Diagnostic and Laser Measurements in PDT -- Implementation of Laser Technologies in Clinical PDT -- Photochemical Internatlisation(PCI) -- A Novel Technology for Targeted Macromolecule Therapy -- Part IV Oncological Applications -- PDT in Dermatology -- Photodynamic Diagnosis and Therapy for Brain Malignancies: From the Bench to Clinical Application -- Photodynamic Therapy for Thoracic Oncology -- Photodynamic Therapy for Polypoidal Choroidal Vasculopathy -- Part V Non-Oncological Applications -- Functional Targeting of Bacteria: A Multimodal Construct for PDT and Diagnostics of Drug-Resistant Bacteria -- Photodynamic Therapy: A Novel Promising Approach for the Treatment of Spontaneous Microbial Infections in Pet Animals -- Photodynamic Control of Noxious Insects and Parasites.
Keywords: Chemistry; Oncology; Chemistry, Physical organic; Microwaves; Chemistry; Physical Chemistry; Medical and Radiation Physics; Cancer Research; Oncology; Microwaves, RF and Optical Engineering